PSIKOEDUKASI KESEHATAN MENTAL PADA SISWA KELAS X SMA BATIK 1 SURAKARTA - Nugroho, Novan; Purnomosidi, Faqih (FIP UNIRA MALANG, 2025)
In recent years, the increasing cases of mental health disorders among adolescents, especially high school students, have become an increasingly emerging issue. Given that adolescence is a crucial stage of development that is very vulnerable to psychological problems, intervention through psychoeducation is important. Psychoeducation aims not only to provide an understanding of mental health, but also to encourage students to care more about their own and others' psychological conditions. This study is important to determine the extent to which psychoeducation is effective in increasing students' collective awareness to maintain each other's mental health, especially in the school environment. Psychoeducational activities were carried out in the form of a survey filling out a google form about how important mental health is for students and delivering material entitled